2022
DOI: 10.3390/cancers14246096
|View full text |Cite
|
Sign up to set email alerts
|

Oral Microbiome in Nonsmoker Patients with Oral Cavity Squamous Cell Carcinoma, Defined by Metagenomic Shotgun Sequencing

Abstract: Objectives: Smoking is the commonest cause of oral cavity squamous cell carcinoma (OC-SCC), but the etiology of OC-SCC in nonsmokers is unknown. Our primary goal was to use metagenomic shotgun sequencing (MSS) to define the taxonomic composition and functional potential of oral metagenome in nonsmokers with OC-SCC. Methods: We conducted a case–control study with 42 OC-SCC case and 45 control nonsmokers. MSS was performed on DNA extracted from mouthwash samples. Taxonomic analysis and pathway analysis were done… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…Therefore, future studies should examine the mycobiome as well as the microbiome in any microbiological investigative studies. Although not included in our search criteria it is noteworthy that there are additional considerations other than the microbiome and mycobiome, including the phageome, virome and meta‐transcriptome with the oral environment (56).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, future studies should examine the mycobiome as well as the microbiome in any microbiological investigative studies. Although not included in our search criteria it is noteworthy that there are additional considerations other than the microbiome and mycobiome, including the phageome, virome and meta‐transcriptome with the oral environment (56).…”
Section: Discussionmentioning
confidence: 99%
“…Functional differences were also analysed in these metagenomic studies. Two studies concordantly reported a decrease in nucleotide metabolism and amino acid metabolism in cancer patients [ 103 , 104 ]. Ganly et al [ 103 ] also noted an increase in OSCC patients of several biosynthesis pathways, including vitamins, heme, sugars, and fatty acids (flavin, biotin, and thiamine).…”
Section: Oral Carcinomamentioning
confidence: 92%
“…Two studies concordantly reported a decrease in nucleotide metabolism and amino acid metabolism in cancer patients [ 103 , 104 ]. Ganly et al [ 103 ] also noted an increase in OSCC patients of several biosynthesis pathways, including vitamins, heme, sugars, and fatty acids (flavin, biotin, and thiamine). In contrast, folate biosynthesis, anaerobic energy metabolism, and pyruvate fermentation pathways were reported to be less active in OSCC patients.…”
Section: Oral Carcinomamentioning
confidence: 92%
See 2 more Smart Citations